SIMBOLISASI DALAM NOVEL SANG ALKEMIS KARYA PAULO QUELHO - Endang Maruti (STKIP PGRI Jombang, 2019)
The research aims to uncover the symbols in the novel The Alchemist and to gain knowledge about the moral teachings in the symbol. This research is descriptive qualitative approach. Data sources in this study are words, phrases or sentences in the novel Alchemist. Data collection method is a literature study method with note taking technique. Data were analyzed using description and content analysis methods. The results showed that the novel The Alchemist contained many symbols. These symbols include: (1) wise parents, who symbolize both negative and positive things. From his appearance, parents can symbolize something bad, but behind his old age he symbolizes a knowledge that is very much and wise; (2) stones that symbolize something hard, not easily broken, and can provide clues to something; and (3) deserts or deserts which can be interpreted as symbols of drought, aridity, unattractiveness, emptiness, despair, determination for ignorance, and also as symbols of devotion.